Optimal Intrathecal Hyperbaric Bupivacaine Dose With Opioids for Cesarean Delivery: A Prospective Double-blinded Randomized Trial. Issue 2 (June 2018) - Onishi, E.; Murakami, M.; Hashimoto, K.; Kaneko, M.
Abstract : ( Int J Obstet Anesth . 2017;31:68–73) Single-shot spinal anesthesia is one of the most common anesthetic techniques for cesarean delivery. When choosing the dose of hyperbaric bupivacaine to use for this procedure, one must balance the need for a dose that will achieve adequate anesthesia for the duration of the surgery while avoiding the complications such as hypotension associated with higher doses. In this prospective, randomized, double-blinded, dose-ranging trial conducted between 2010 and 2013 at a single hospital in Japan, the researchers goal was to identify the ideal dose of intrathecal hyperbaric bupivacaine, coadministered with opioids, for cesarean delivery.